2019
DOI: 10.3390/medicina55120753
|View full text |Cite
|
Sign up to set email alerts
|

The Role of C21orf91 in Herpes Simplex Virus Keratitis

Abstract: Background and Objectives: This paper aims to describe the single nucleotide polymorphisms (SNPs) of C21orf91 rs1062202 and rs10446073 in patients with herpetic keratitis by evaluating corneal sub-basal nerves, as well as the density of Langerhans cells (LC) and endothelium cells (EC) during the acute phase of the disease. Materials and Methods: A prospective clinical study included 260 subjects: 70 with herpetic eye disease, 101 with previous history of herpes labialis—but no history of herpetic eye disease—a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Also, previous studies have indicated that the C21ORF91 gene encoding cytosolic protein plays a role in biological processes, such as cerebral cortex neuron differentiation, cell differentiation and regulation of dendritic spine development (Danileviciene et al, 2019). Recently, few researches show relationship between the C21ORF91 gene and herpes labialis, in which C21ORF91 gene is identified as direct targets of miR-194 in hepatocellular carcinoma cells (HCC) (Kriesel et al, 2011;Bao et al, 2015), but its function is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Also, previous studies have indicated that the C21ORF91 gene encoding cytosolic protein plays a role in biological processes, such as cerebral cortex neuron differentiation, cell differentiation and regulation of dendritic spine development (Danileviciene et al, 2019). Recently, few researches show relationship between the C21ORF91 gene and herpes labialis, in which C21ORF91 gene is identified as direct targets of miR-194 in hepatocellular carcinoma cells (HCC) (Kriesel et al, 2011;Bao et al, 2015), but its function is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Danileviciene et al [ 154 ], identified the role of the C21orf91 gene in the development of HSK where they described the condition to be 2.9 times more likely in patients with the rs10446073 genotype being more common[ 154 ]. According to Borivoje et al [ 155 ], the CC IL28B gene has been identified to be present in individuals with recurrent HSK[ 155 ].…”
Section: Diagnostic Approaches For Herpes Simplex Keratitis: Challeng...mentioning
confidence: 99%
“…Matoba also presented a patient with herpetic stroma keratitis, under oral acyclovir and topical prednisolone acetate treatment, who developed polymicrobial keratitis including B. ambifaria (belonging to the B. cepacia complex), Enterococcus spp., and Staphylococcus aureus[7]. Infection with herpes virus might cause sub-basal nerve damage of the cornea[12,13]. The impaired corneal sensory innervation leads to a reduction of protective reflexes and trophic neuromodulators, which affect the wound-healing function of the cornea[14], making its surface an easy target for opportunistic bacteria such as B. cepacia.…”
mentioning
confidence: 99%